Analysis of the Reality of Fiscal Discipline in Iraq for the Period (2014-2024) - Harith Raheem Atiyah Yas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Fiscal discipline constitutes a fundamental pillar of macroeconomic stability, ensuring balance between public revenues and expenditures while safeguarding fiscal sustainability. Specific Background: During 2014–2024, Iraq’s public finances were shaped by excessive reliance on oil revenues, security shocks, oil price volatility, and expansionary expenditure patterns. Knowledge Gap: Despite Iraq’s substantial oil wealth, limited empirical synthesis has examined the structural gap between fiscal potential and actual fiscal performance using integrated indicators of budget deficit, public debt, expenditure ratios, and tax revenues. Aims: This study analyzes the reality of fiscal discipline in Iraq over the period 2014–2024 and evaluates its role in explaining persistent budget deficits, rising public debt, and weak revenue diversification. Results: The findings confirm a structural imbalance characterized by recurrent deficits exceeding international benchmarks in several years, public debt ratios reaching critical levels, government expenditure consistently surpassing the 30% safety threshold of GDP, dominance of current over investment spending, and marginal tax contributions rarely exceeding 2% of GDP. Fiscal performance remained highly procyclical, expanding during oil booms and deteriorating during shocks, thereby reinforcing financial fragility. Novelty: The study provides a comprehensive indicator-based assessment linking fiscal rules, expenditure structure, debt dynamics, and revenue composition within a unified analytical framework for Iraq. Implications: Achieving fiscal sustainability requires expenditure rationalization, strengthening non-oil revenues, institutionalizing fiscal rules, and adopting structural reforms to reduce oil dependency and restore long-term macroeconomic stability. Highlights: Recurrent Imbalances Were Closely Tied to Oil Price Volatility and Security Shocks. Government Spending Frequently Exceeded Internationally Accepted Safety Ratios Relative to GDP. Non-Oil Revenue Mobilization Remained Structurally Weak Despite Periods of Revenue Expansion. Keywords: Fiscal Discipline; Budget Deficit; Public Debt; Oil Revenue Dependency; Fiscal Sustainability